Registros de grandes alagamentos no cânion do Rio Peruaçu, Parque Nacional Cavernas do Peruaçu PNCP, MG - Ataliba Henrique Fraga Coelho (2013)
Reports of flooding, due to large volumes of breakdown deposits in the Peruaçu river canyon, located in Cavernas do Peruaçu National Park, Minas Gerais, have been made by researchers in the last decades (Piló, 1989, 1991, 1997, 2002, 2008; Rubbioli, 1999; Rodet & Rodet, 2001; Ferreira, 2003; Piló et al., 2005; Oliveira, 2008 and Rodet et al., 2004, 2009). As records, these floods have left trunks and watermarks at an elevated position inside the caves. This research aimed to identify these records and build a topographic profile that would permit the correlation between their altimetry, as well as morphological and depositional elements of the canyon, in order to identify points of obstruction of river flow. The comparison between the ages of the events, by means of C14 dating, was also an objective. The work focused on the stretch upstream of the canyon, between Carlúcio and Troncos caves, where a longitudinal topographic profile was designed containing the records altimetry, as well as the representation of the stretchs morphological and depositional features. Through cartographic analyses and field observations, two points of obstruction were identified: one upstream, inside Lapa da Onça, with a capacity to hold runoff up to the quota of 676 m (+ 46 m above the present level of the Peruaçu river); one downstream, at Arco do André, capable of holding water up to 653 m elevation (+53 m). Watermarks were identified inside the caves: Lapa da Onça (M-1: + 36 m) and Arco do André (M-2: + 41 m and M-3: + 53 m). Chronological data indicated that the flooding of two sectors were contemporaneous and are quite recent, having occurred between approximately 1,600 and 100 years ago. This may be related to the maximum limit of preservation of plant remains inside caves. The ages obtained discard the possibility that these large floods are related to a wetter climate in the past, and are probably due to blockage of underground routes and / or extreme rainfall events. Correlation between elevation and chronological data allowed inferring that there were at least six flooding events which deposited trunks inside Carlúcio, Brejal and Arco do André caves. These events were generated by obstruction at Lapa da Onça: Gr-01 (1590 ± 20 BP); Gr-03 (between 750 ± 20 and 800 ± 20 AP); Gr-04 (510 ± 30 AP) and Gr-05 (between 340 ± 20 and 390 ± 25 AP), and in Arco do André: Gr-01 (1610 ± 50 BP), Gr-02 (1380 ± 20 BP) and Gr-06 (between 100 ± 25 and 140 ± 25 AP). The close ages assigned to the Gr-01 event are related to obstruction at Lapa da Onça and Arco do André caves, and may indicate overflow above the elevation of 676 m at Lapa da Onça, as well as flooding of the stretch downstream. The topographic profile showed that important slopes occur along the Peruaçu river channel, associated with the segments covered by clastic sediments. Morphological analysis showed that sinkhole coalescence is an important process in the evolution of the Peruaçu river karst.